Theory of Planned Behaviour and its Applications in Marketing Contexts: A Systematic Literature Review and Future Directions - Sukri, Sukri; Evanita, Susi; Dwita, Vidyarini (Yayasan Sinergi Kawula Muda, 2026)
This study employs a Systematic Literature Review (SLR) combined with bibliometric analysis to examine the evolution of the Theory of Planned Behaviour (TPB) in marketing research. Drawing on 55 Scopus- and Web of Science–indexed articles published between 2021 and 2025, VOSviewer is used to map research trends and thematic structures. The findings show that core TPB constructs remain central predictors of consumer intention, while extensions such as trust, perceived risk, and moral norms increasingly enhance explanatory power in digital and sustainability contexts. However, challenges persist, including the intention–behaviour gap and limited cross-cultural validation. This study advances marketing theory by proposing an integrative framework linking psychological, technological, and contextual factors to support sustainable and consumer-oriented marketing strategies.